High-frequency promoter hypermethylation of the deleted in liver cancer-1 gene in multiple myeloma. Issue 9 (17th February 2006) - Song, Y-F; Xu, R; Zhang, X-H; Chen, B-B; Chen, Q; Chen, Y-M; Xie, Y
Abstract : Background: Deleted in liver cancer-1 ( DLC-1 ) is a tumour suppressor gene that is inactive in liver carcinogenesis. It encodes a ρ-guanosine triphosphatase-activating protein (ρ-GAP) and maps to one of the deleted regions (8p21.3–22). Little is known, however, about the methylation status of the DLC-1 promoter in myeloma cells. Aim: To identify whether methylation of DLC-1 was associated in pathogenesis of multiple myeloma. Methods: Reverse transcription-polymerase chain reaction (RT-PCR) was used to detect DLC-1 transcripts in RPMI 8226, U266, OPM-2 and XG-2 cell lines. The methylation status was determined by methylation-specific PCR followed by bisulphite DNA sequencing in these four cell lines and in the bone marrow of 14 patients with multiple myeloma and 4 normal patients. DLC-1 mRNA expression in cells with or without treatment with 5-aza-deoxycytidine (5-aza-CdR) or trichostatin A (TSA) was investigated by real-time RT-PCR. Results: RPMI 8226 and U266 showed complete methylation and XG-2 showed partial methylation. DLC-1 was expressed only in OPM-2 cell lines that showed no methylation. DLC-1 methylation was shown in 11 of 14 (78%) patients with multiple myeloma and none of the normal controls. The exposure of cell lines to 5-aza-CdR or TSA resulted in the up regulation of DLC-1 gene expression. Conclusions: DLC-1 methylation is often present in multiple myeloma and has a key role in DLC-1 silencing.